FLOOD-PLAIN UTILIZATION IN SOME BEDADUNG’S SUB-WATERSHED FOR PADDY CULTIVATION IN ORDER TO SUPPORT FOOD SECURITY - S A Budiman (UPT Penerbitan Universitas Jember, 2012)
Along with the rapid growth of population on Java island, many land-uses werechange as residential and agricultural-field. One consequence of these conditions was theincreased sensitivity of the environment against climate change like floods in the rainyseason and drought in the dry season. The purpose of study were identifying the floodplainarea in several sub-watershed in Bedadung’s watershed due to utilization of paddycultivation as an alternative to use of marginal land to reduce the rate of catchmentdeforestation. The research was conducted in several sub-watershed that are part of theBedadung watershed i.e : Kaliputih, Dinoyo and Kaliwates. Soil characteristics andclimatic data were collected from Bappeda Jember, BP-DAS and BMKG. Sub-watershedboundary was identified using Indonesia’s Earth Map scale 1: 50,000, while thefloodplains, land uses and slope based identifified by satellite imagery. Image analysisperformed by open source GIS software, and the risk of crop failure analysis obtained fromthe data overlay cropping patterns and the incidence of flooding during the last 20 years.The results showed that the the largest floodplain that can be utilized for paddy cultivationexpansion was in Kaliputih (48.02%), whereas the highest production level achieved by theDinoyo and Kaliputih (70 tons) and the highest level of productivity achieved by theKaliwates and Dinoyo (4 ton.ha). Level of risk of crop failure due to environmentalsensitivity in each sub-watershed was 67% for Kaliputih, 48% for Kaliwates and a 35% forDinoyo.